Can the integration between Islamic social finance and Islamic commercial finance tackle poverty in Indonesia? - Siswantoro Siswantoro (Jurnal Ekonomi & Keuangan Islam, 2022)
Purpose – This study aims to examine the effects of Islamic social finance, Islamic commercial finance, and the integration of Islamic social finance and Islamic commercial finance on poverty in Indonesia.Methodology – Data in the form of time series from 2002 to 2021 were evaluated using the Error Correction Model (ECM) approach. This method describes both long and short-term effects of Islamic social finance, Islamic commercial finance, and integration of Islamic social finance and Islamic commercial finance on poverty.Findings – The results show that Islamic social finance, Islamic commercial finance, and the integration between the two Islamic finance sectors have a significant negative effect on poverty rates in the long term. In the short term, the integration between Islamic social finance and Islamic commercial finance has a significant negative effect on the poverty rate, while Islamic social finance and Islamic commercial finance have a negative but not significant effect on the poverty rate.Implication – This study recommends policymakers make rules regarding the implementation of collaborative efforts on institutions in the two Islamic finance sectors in the future.Originality – Most of the studies that have been conducted have only focused on one sector of Islamic finance. In fact, the integration between Islamic social finance and Islamic commercial finance in Indonesia makes these two sectors of Islamic finance have the potential to reduce poverty higher than without integration.